Rice Production and Weed Management as Affected by Salinity - Hakim, Md. Abdul (2011)
Salinity and weeds are major constraints to rice production in Peninsular Malaysia. Rice yield reduction is caused by salinity due to its adverse effect on many important physiological processes. On the other hand, weeds cause yield reduction by competition and allelopathy effect. The present study was therefore designed to select salt tolerant rice varieties and weed species, and also to develop a suitable weed management strategies for rice under saline environments. Surveys were conducted in three major rice growing coastal areas (Seberang Perak, Tanjong Karang, and Muda, Kedah) in Peninsular Malaysia and the results revealed that there were 53 different weeds in the coastal area having 12 grasses, 13 sedges and 28 broadleaved species. Based on relative abundance, the ten most dominant weed species in surveyed area were: Echinochloa crusgalli, Fimbrystylis miliacea, Leptochloa chinensis, Echinochloa colona, Cyperus iria,Jussia linifolia, Oryza sativa L. (weedy rice), Sphenoclea zeylanica, Cyperus defformis and Scirpus grossus. Germination of twelve rice varieties were studied at six salinity levels in the laboratory and the results showed that MR211, MR232 and IR20 were tolerant and MR33, MR52, MR219 and BRRI dhan40 were moderately tolerant based on germination percentage, germination index, vigor index at 4 DAS and dry matter production. Subsequent studies on growth, biochemical constituents, mineral composition and yield response of eight rice varieties to different salinity levels in the glass house revealed that growth of rice plants was arrested instantly at 12 dS m-1. However, MR232 and MR211 were graded as salt tolerant, while MR52 and MT33 were found to be moderately tolerant. Germination of ten weed species were studied under different salinity levels in laboratory and it was found that C. iria and E. colona showed superior, while E. crusgalli, J. linifolia, L. chinensis and O. sativa L. (weedy rice) were moderate in terms of seed germination and seedling vigor. Subsequently, the growth and ion accumulation response of six weed species to different salinity levels was studied in the glass house. The results revealed that C. iria, E. colona and E. crusgalli were relatively tolerant, J. linifolia and L. chinensis moderately tolerant based on growth performance, chlorophyll contents, proline contents and ion accumulation. Critical period of rice-weed cometition was studied in a glass house under saline environment and the results showed that the critical period for weed competition under 5% yield loss at 0, 4 and 8 dS m-1 were 14 to 55, 12 to 64 and 7 to 80 days after transplanting (DAT), respectively. The critical period for 10% yield loss at 0, 4 and 8 dS m-1 were 36 to 45, 32 to 48 and 23 to 64 DAT, respectively. Weed control efficacy of different herbicides under three salinity levels was also evaluated in the glass house and the results revealed that pretilachlor (Sofit®) @ 0.375 kg ai/ha, propanil + thiobencarb (Satunil®) @ 0.9 kg ai/ha + 1.8 kg ai/ha, bensulfuron (Tekong®) + MCPA @ 0.06 kg ai/ha +0.1 kg ai/ha and pretilachlor @ 0.50 kg ai/ha treatments performed better in terms of weed biomass,weed control efficiency, rice injury rating, rice growth and yield performance. The results showed that higher than recommend rates caused toxicity to rice plants under saline environment. Consequently, among the treatments pretilachlor (Sofit®) @ 0.375 kg ai/ha + one round of hand weeding (at 65 DAT), propanil + thiobencarb (Satunil®) @ 0.9 kg ai/ha + 1.8 kg ai/ha + one round of hand weeding (at 65 DAT) performed better considering the critical period, which was superior under saline environment. Based on the results of the present investigation, it may be concluded that MR232 rice variety can be selected for the coastal zone of Peninsular Malaysia, and major salt tolerant weeds in the rice field may be controlled by considering the critical period of rice-weed competition and spraying herbicides like pretilachlor (Sofit®) @ 0.375 kg ai/ha at 4 DAT followed by one round of hand weeding (at 65 DAT) or propanil + thiobencarb (Satunil®) @ 0.9 kg ai/ha + 1.8 kg ai/ha at 10 DAT followed by one round of hand weeding (at 65 DAT).